Surface and Catalytic Properties of Copper Oxide, Manganese Oxide/Silica Systems - Nagi R.E. Radwan (Adsorption Science & Technology)
Various CuO/SiO 2 , Mn 2 O 3 /SiO 2 and CuO–Mn 2 O 3 /SiO 2 systems having different compositions were prepared using a wet impregnation method employing finely powdered SiO 2 solid. The CuO content was varied in the range 5–20 wt% whilst that of Mn 2 O 3 was changed in the range 5–30 wt%. In the tertiary systems studied, the Mn 2 O 3 content was fixed at 5 wt% whilst that of CuO was 5 wt% and 10 wt%, respectively. The supported solids thus obtained were subjected to heat treatment at 300–700°C and the crystalline phases produced identified by XRD methods. The surface and catalytic properties of the various calcined solids were studied by nitrogen adsorption at −196°C and studies of the catalyzed decomposition of H 2 O 2 in aqueous solution at 30–50°C. The results obtained revealed that although the silica support material employed was normally amorphous in nature when calcined at 500°C and 700°C, it crystallized after treatment with CuO followed by calcination at 700°C. Diffraction lines corresponding to CuO and SiO 2 phases were detected in the XRD patterns of all CuO-treated silica samples calcined at 700°C. In contrast, only diffraction lines for a poorly crystallized Mn 2 O 3 phase were observed in the patterns for all Mn 2 O 3 -treated silica samples calcined at this temperature. The specific surface areas of the systems investigated were found to decrease on increasing both the extent of loading and the calcination temperature. Thus, after calcination at 300°C, all the various systems examined contained mainly narrow pores whose diameter increased after calcination at 700°C; nevertheless, these adsorbents behaved as mesoporous materials. Their catalytic activity was strongly dependent on the extent of loading and the calcination temperature employed. The activation energy of the catalyzed reaction conducted over the various solids examined was not greatly affected by the extent of loading. When expressed in terms of the reaction rate constant per unit surface area (k̄), the catalytic activity for the catalyzed reaction carried out at different temperatures over the various solids decreased in the order: CuO–Mn 2 O 3 ,/SiO 2 > Mn 2 O 3 –CuO/SiO 2 > Mn 2 O 3 ,/SiO 2 > Mn 2 O 3 > CuO/SiO 2 . The mechanisms for the catalytic reaction in contact with the various solids were discussed.